Eeflexive perspective on instructional objectives for medical school teachers of the Decanato de Ciencias de la Salud (Boletin Médico de Postgrado, 2020)
This essay tries to analyze and reflect about the instructional objectives that are being taught at the Universidad Centroccidental Lisandro Alvarado, specifically at the Decanato de Ciencias de la Salud. We present four steps to guide on how the teaching-learning process should be so the teachers and students meet their planned goals.
Keywords: instructional objectives; teaching; learning